2019
DOI: 10.26444/aaem/91471
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability Index (WAI) values in a sample of the working population in Poland

Abstract: Introduction. Ability to work is most often defined as a relationship between a person's resources and requirements specific to a particular type of work. It is the result of interaction between job requirements in terms of physical and mental strain, capabilities and skills of the employee, as well as his/her health condition and own evaluation of functioning in a given organizational and social situation. Objective. The primary objective of the study was to evaluate the current value of the Work Ability Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
9
0
4
Order By: Relevance
“…The current work found that the old age group (≥ 40 years) was less likely to have a better response in most dimensions of WAI (Table 3). Older healthcare providers had lower odds for optimal WAI which support the previous findings of most studies that reported a decreased WAI with older age (Monteiro et al, 2006;Golubic et al, 2009;El Fassi et al, 2013;Mehrdad et al, 2016;Heyam et al, 2018), while other studies demonstrated no association (Juszczyk et al, 2019 andPranjic et al, 2019). With old age, the physical and mental skills will be reduced due to suffering from various health problems and chronic diseases which can limit the ability to work (Converso et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The current work found that the old age group (≥ 40 years) was less likely to have a better response in most dimensions of WAI (Table 3). Older healthcare providers had lower odds for optimal WAI which support the previous findings of most studies that reported a decreased WAI with older age (Monteiro et al, 2006;Golubic et al, 2009;El Fassi et al, 2013;Mehrdad et al, 2016;Heyam et al, 2018), while other studies demonstrated no association (Juszczyk et al, 2019 andPranjic et al, 2019). With old age, the physical and mental skills will be reduced due to suffering from various health problems and chronic diseases which can limit the ability to work (Converso et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The WAI questionnaire includes the following dimensions of the individuals: their current ability to work in comparison with their best years of life; their ability to work concerning their demand for work; the number of diagnosed diseases or limitations from which they suffer; their estimated impairments due to diseases/abilities or limitations; the number of sick leaves they have taken during the last year; the projections of their ability to work for 2 years (Juszczyk et al, 2019). Previous studies confirmed the validity and reliability of the WAI tool (Abbasi et al, 2016;Abdolalizadeh et al, 2012;Ebener & Hasselhorn, 2019;Peralta et al, 2012).…”
Section: Research Toolmentioning
confidence: 99%
“…There is strong evidence demonstrating that fast changes in the nature of work and technology will require workers with new skills to fill labor market needs created by population aging [2]. Both hard and soft skills are needed; an excellent technical understanding of emerging digital technologies and communication, critical thinking, and persuasion are required [2,6]. Healthy workers and decent work refer to the need for aspirations for people in their working lives, relating to protecting labor rights, promoting safe and secure working environments [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as lifestyle (e.g., leisure-time physical activity, diet, smoking and sleep) [13][14][15] and work environment (i.e., chemical hazards, psychological and ergonomics) [16] may also affect WA. Previous studies found that those hazards lead to health problems, including cardiovascular disorder, stress, mental health, respiratory symptoms, musculoskeletal disorder, and accidents [6,8,[17][18][19][20]. Thus, balancing work ability and work demand is a concern due to health effects, work capability and quality of life [16].…”
Section: Introductionmentioning
confidence: 99%